Migratory birds benefit from urban environments in a highly anthropized Neotropical region - Rodrigo Pacheco-Muñoz; Adrián Ceja-Madrigal; Jorge E. Schondube (PLoS ONE, 2025)
Land use change from wildlands to urban and productive environments can dramatically transform ecosystem structure and processes. Despite their structural and functional differences from wildlands, human-modified environments offer unique habitat elements for wildlife. In this study, we examined how migratory birds use urban, productive, and wildland environments of a highly anthropized region of Western Mexico known as “El Bajío”. We used Generalized Linear Models to compare species richness, abundance, and the functional traits of migratory bird assemblages among these three environments. Results revealed differences in species richness, composition, and the functional traits of migratory birds among environments. Regardless of wildlands showing medium to high levels of human disturbance, they presented the highest species richness and abundance of migratory birds, with urban environments presenting the lowest values. Insectivorous and granivorous birds were dominant in the migratory bird assemblages of the three environments. The migratory bird assemblages of productive environments had more grassland granivorous birds. In contrast, insectivorous birds with dense habitat preferences and short culmen lengths dominated the urban bird assemblage. Migratory bird assemblages in productive and urban environments showed similar species richness and abundance of insectivorous birds, but they differ in their composition. Our results reveal that urban trees allowed cities to function as simplified forests, showing that the urban environment has the untapped potential to support complex assemblages of migratory birds. To promote migratory birds in human-modified landscapes, we must maintain complex vegetation areas that allow birds with diverse functional traits to overwinter in urban and productive environments.